2011
DOI: 10.4297/najms.2011.3185
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lactobacilli and opportunistic bacterial pathogens associated with vaginitis

Abstract: Background:Vaginitis, is an infectious inflammation of the vaginal mucosa, which sometimes involves the vulva. The balance of the vaginal flora is maintained by the Lactobacilli and its protective and probiotic role in treating and preventing vaginal infection by producing antagonizing compounds which are regarded as safe for humans.Aim:The aim of this study was to evaluate the protective role of Lactobacilli against common bacterial opportunistic pathogens in vaginitis and study the effects of some antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 28 publications
6
41
4
2
Order By: Relevance
“…There is currently no standardized treatment for AV infected mothers to reduce the rate of adverse pregnancy outcomes 18 , although treatment during the second trimester of pregnancy has been advocated 10 . The effects of screening and treatment for abnormal vaginal microbiota in order to reduce preterm delivery (PTD) remain controversial 21 with low prevalence of AV reported in some studies 11,91 and others showing a very high prevalence 92,93 . Interventions to prevent pre-term birth have been largely ineffective 1,2 and may be attributed to both the increasing antimicrobial resistance amongst opportunistic pathogens which complicates adequate administration of prophylaxis and treatment as well as the often misdiagnosis of AV as BV, thus leading to treatment failures and thereby contributing to and increasing the risk of maternal and neonatal morbidity.…”
Section: Resultsmentioning
confidence: 99%
“…There is currently no standardized treatment for AV infected mothers to reduce the rate of adverse pregnancy outcomes 18 , although treatment during the second trimester of pregnancy has been advocated 10 . The effects of screening and treatment for abnormal vaginal microbiota in order to reduce preterm delivery (PTD) remain controversial 21 with low prevalence of AV reported in some studies 11,91 and others showing a very high prevalence 92,93 . Interventions to prevent pre-term birth have been largely ineffective 1,2 and may be attributed to both the increasing antimicrobial resistance amongst opportunistic pathogens which complicates adequate administration of prophylaxis and treatment as well as the often misdiagnosis of AV as BV, thus leading to treatment failures and thereby contributing to and increasing the risk of maternal and neonatal morbidity.…”
Section: Resultsmentioning
confidence: 99%
“…7,19 80.77% of cases yielded monomicrobial growth whereas 19.23% yielded polymicrobial growth (two bacterial species in culture) which is in contrast to study done by Razzak et al, 2011 (Iraq) who observed 50 out of 105 cases (47.62%) as polymicrobial infections. 15 In this study, Enterococcus faecalis (32.26%) was the most prevalent organism isolated from AV cases followed by Escherichia coli (25.8%) and Staphylococcus aureus (22.6%). In a study by Khan and khan in Islamabad (2004), Enterococcus faecalis (31%) was the most frequently isolated aerobic vaginal pathogen.…”
Section: Discussionmentioning
confidence: 64%
“…Similar rates have been observed by Mumtaz et al 17 The isolation of K pneumoniae and Pseudomonas aeruginosa in AV cases was also reported by other researchers. 13,15,17 The gram positive organisms in this study showed more resistance to penicillin and ampicillin. Nearly 40 % of the Enterococcus isolates were resistant to penicillin and ampicillin whereas only 10% of them showed resistance to aminoglycosides which is in contrast to other studies.…”
Section: Discussionmentioning
confidence: 64%
“…L. jensenii and L. gasseri are two of the most common species present, as determined by culture-independent techniques [4]. Relationship between LAB and vaginal pathogen have been studied which indicates that antibiotic treatment should not kill healthy LAB to preserve healthy vagina [4].…”
Section: Introductionmentioning
confidence: 99%